2020
DOI: 10.1111/apa.15324
|View full text |Cite
|
Sign up to set email alerts
|

Paediatricians provide higher quality care to children and adolescents in primary care: A systematic review

Abstract: Aim The number of primary care paediatricians is decreasing in Europe without a justifiable reason. We aimed to compare the clinical practice of paediatricians and family doctors attending children and adolescents in primary care. Methods MEDLINE, Embase, CENTRAL, TRIP and Google Scholar were searched from December 2008 to February 2018. No language or study design restrictions were applied. Three reviewers assessed eligibility of the studies. Seven pairs of reviewers performed the data extraction and assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Although the heterogeneity of the studies did not allow for a rigorous meta-analysis, the data showed that in 62.5% of the studies antibiotic prescription by pediatricians was reported to be more appropriate and in line with official clinical practice guidelines. 21,27…”
Section: Appropriateness Of Antibiotic Prescriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the heterogeneity of the studies did not allow for a rigorous meta-analysis, the data showed that in 62.5% of the studies antibiotic prescription by pediatricians was reported to be more appropriate and in line with official clinical practice guidelines. 21,27…”
Section: Appropriateness Of Antibiotic Prescriptionmentioning
confidence: 99%
“…The systematic AEPap review indicates that pediatricians were more accurate than generalists in assessing the nutritional status of children and adolescents and in following the guidelines for diagnostic procedures and preventive programs for these conditions. 21,27,28 Finally, the review reports that pediatricians were more diligent than GPs or other specialists in areas of clinical practice, such as the use of laboratory tests in the diagnosis and management of different conditions (streptococcal, celiac disease, diabetes mellitus, and early diagnosis of acute lymphoblastic leukemia), and referring to specialists for the pharmacologic treatment of psychiatric disorders. 27…”
Section: The Contribution Of Pediatricians To Prevention Programs and Laboratory Testing Adequacymentioning
confidence: 99%